1992
DOI: 10.1073/pnas.89.18.8626
|View full text |Cite
|
Sign up to set email alerts
|

Multiple kinase arrest points in the G1 phase of nontransformed mammalian cells are absent in transformed cells.

Abstract: We have shown that nontransformed mammalian cells arrest early in the G1 phase of the cell cycle when treated with exceedingly low concentrations of the nonspecific kinase inhibitor staurosporine, whereas transformed cels continue to progress through the cell cycle. We have now treated normal or transformed human skin fibroblasts with four other kinase inhibitors. Three of these inhibitors are highly specific: KT5720 inhibits cAMP-dependent protein kinme, KT5823 inhibits cGMP dependent protein kinase, and KT59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 24 publications
(25 reference statements)
4
68
0
Order By: Relevance
“…However, we could not completely rule out the involvement of protein kinase C (K i =4 mM). 15 2,6 In the present study, we found that atrial natriuretic peptide and nitric oxide, through their action on PKG, inhibited the flow-induced [Ca 2+ ] i entry in M1-CCD cells. Previously, atrial natriuretic peptide and nitric oxide were known to inhibit Na + reabsorption in CCD.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, we could not completely rule out the involvement of protein kinase C (K i =4 mM). 15 2,6 In the present study, we found that atrial natriuretic peptide and nitric oxide, through their action on PKG, inhibited the flow-induced [Ca 2+ ] i entry in M1-CCD cells. Previously, atrial natriuretic peptide and nitric oxide were known to inhibit Na + reabsorption in CCD.…”
Section: Discussionmentioning
confidence: 66%
“…KT5823 is a highly selective inhibitor for PKG, with K i =0.234 mM. 15 At the concentration that we used (1 mM), it should not affect protein kinase A (K i .10 mM). However, we could not completely rule out the involvement of protein kinase C (K i =4 mM).…”
Section: Discussionmentioning
confidence: 99%
“…CREB transcriptional activity is regulated by its phosphorylation on Ser 133 by protein kinase A enzymes. To confirm our results obtained using the KCREB dominant-negative expression vector, Mono-Mac-1 cells were transfected with the P2-1900 reporter and treated with KT-5720, a potent cAMP-dependent protein kinase inhibitor (67,68) prior to and during infection with HHV-6. Our results clearly show a dose-dependent inhibition of promoter activity with KT-5720 (Fig.…”
Section: Effects Of Protein Kinase Inhibitors On the Hhv-6-related Comentioning
confidence: 99%
“…The induced expression of ␥-globin mRNA by PPIX, however, was abolished by preincubating the cells with the sGC inhibitor LY83583 (31), or with KT5823, which is a selective inhibitor of PKG (ref. 32; Fig. 4A, lanes 4 and 5).…”
Section: Expression Of the ␥-Globin Gene Is Induced By Activating Thementioning
confidence: 99%